Effects of the cyberbullying prevention program media heroes (Medienhelden) on traditional bullying. Issue 2 (March 2016) - Chaux, Enrique; Velásquez, Ana María; Schultze‐Krumbholz, Anja; Scheithauer, Herbert
Abstract : There is considerable debate over whether cyberbullying is just another form of bullying, or whether it is a problem distinct enough to require specific intervention. One way to explore this issue is to analyze whether programs designed to prevent traditional bullying help prevent cyberbullying, and whether programs designed to prevent cyberbullying prevent traditional bullying. The main goal of the current study was to analyze the spillover effects of the cyberbullying prevention program Media Heroes ( Medienhelden ) on traditional bullying. Media Heroes promotes empathy, knowledge of risks and consequences, and strategies that allow bystanders to defend victims from cyberbullying. Mixed ANOVAs were conducted comparing pretest and post‐test (6 months after intervention) measures of 722 students (ages 11–17) assigned to a long (15 sessions) intervention, a short (1 day) intervention, and a control group. In addition to confirming the previously reported effects on cyberbullying, Media Heroes was found to reduce traditional bullying. Effects were larger for the long‐version of the program than for the short 1‐day version. No effects were found on victimization by either cyberbullying or traditional bullying. Strategies to complement traditional and cyberbullying prevention efforts are discussed. Aggr. Behav. 42:157–165, 2016. © 2016 Wiley Periodicals, Inc.